Geometry of q-hypergeometric functions, quantum affine algebras and elliptic quantum groups - Tarasov V; Varchenko A (Paris Societe Mathematiques de France, 1997)
This paper deals with: Discrete local system, discrete Gauss-Manin connection, quantized Knizhnik-Zamolodchikov equation, tensor coordinates, asymptotic solutions, transition functions
Keywords: Tensor analysis; Vector analysis